Online Learning at Secondary Schools: Listening to Pre-Service Teachers In Their Teaching Practices - Luluk Isnainiyah; Fitriah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
Coronavirus has altered how students are educated and how teachers conduct themselves in the classroom. The changes have compelled educators to shift their primary focus to remote learning or online instruction. Teachers are expected to innovate and digitize learning in order to address the current situation. This study aims to explore pre-service teachers’ perceptions of online learning at secondary schools within an EFL context. The study interviewed five pre-service teachers who had completed teaching practicum at secondary schools as part of their education. The findings indicated that online learning encourages pre-service teachers to access resources from a variety of sources, to exercise their creativity by searching for something different, to expand their knowledge, and to teach with greater flexibility. Although the study discovered positive attitudes toward online learning, these pre-service teachers encountered difficulties in implementing it, including a lack of discipline, slow responses, technical difficulties, and an insufficient internet connection. The study emphasizes how online education encourages pre-service teachers to be more creative in their material selection and professional development. They should, however, ensure that their practice is effective and efficient in reaching out to students.